Climate change risk communication : How message frames shape perceptions of risks and efficacy, and influence behavioural intentions to climate change adaptation and mitigation - Ngo, Chinh Cong (the Netherlands Wageningen University, 2021)
Contents: Introduction; driver of flood and climate change risk perceptions and intention to adapt: an explorative survey in coastal and delta Vietnam; community perceptions of social, economic and environmental impacts of flooding in central districts of Hanoi, Vietnam;...
Keywords: Quản lý tài nguyên & môi trường